Comparative government and politics. An introduction - HAGUE, Rod (Macmillan Publishing Company, 1998)
This fourth edition has been comprehensively revised and rewritten throughout to cover the major changes since the collapse of communism and the end of the Cold War. New chapters have been added on the global context, democracy and democratization, territorial politics, and comparative method and the book has been redesigned throughout into a larger two column format with many editorial and presentational revisions such as full page country case studies, to make it more accessible and student friendly.